Kwara State of Nigeria: your government at work - Kwara State (Nigeria). (Ilorin : Information Division, Military Governor's Office, Kwara State of Nigeria, 1969)
Summary of the activities and achievements of the Kwara State Military Government during ...", 1968/1969; "Summary of the activities and achievements of the Kwara State Military Government covering ...", 1969/1971.
oif 12/04/2019
Loans
Keywords: Executive departments; Administrative agencies; Politics and government; Kwara State (Nigeria); Nigeria